On the Mechanism of Cytoprotection by Ferrostatin-1 and Liproxstatin-1 and the Role of Lipid Peroxidation in Ferroptotic Cell Death & Targeting Tetrahydronaphthyridinols to the Mitochondria - Zilka, Omkar (Université d'Ottawa / University of Ottawa, 2018)
Lipid peroxidation is well established to contribute to the etiology of many deteriorative conditions including neurodegeneration, cardiovascular disease, cancer, aging, and recently in ferroptosis—a regulated, necrotic modality of cell death that results from the accumulation of lipid hydroperoxides. Recent high-throughput screening efforts have uncovered ferrostatin-1 (Fer-1) and liproxstatin-1 (Lip-1) as two premiere inhibitors of ferroptosis. We propose that these compounds function as radical trapping antioxidants. We employ a systematic methodology of evaluating inherent radical trapping antioxidant (RTA) activity of Lip-1, Fer-1, and various aryl amine and aryl nitroxide analogues to put forward a biologically relevant mechanism of action based on our previous work in the field. Joining these observations with the efficacy of tetrahydronaphthyridinols (THNs), the results support a clear role of autoxidation in the execution of ferroptosis. Next, we expand the THN repertoire by targeting the payload towards the engine of our cells, the mitochondria. Decades of research have implicated mitochondrial dysfunction brought about by the peroxidation of mitochondrial membranes and the leaking of downstream oxidants, in the death of their symbiotic host cells. Isolated successes in the field have been demonstrated academically, though viable drugs remain to be developed, partially due to the lack of effective diagnostic tools. We endeavor to address some of these issues by investigating mitochondrially-targeted THNs (MitoTHNs) as a targeted chain-breaking antioxidant of unparalleled potency. Furthermore, we advance development of the THNs towards therapeutic applications by demonstrating their biodistribution in mice.
Keywords: lipid autoxidation; ferroptosis; oxidative stress; mitochondria; radical trapping antioxidant